Effect of Heterologous Expression of Key Enzymes Involved in Astaxanthin and Lipid Synthesis on Lipid and Carotenoid Production in Aurantiochytrium sp. - Yaping Shao; Zhengquan Gao; Fengjie Sun; Yulin Cui; Xinyu Zou; Jinju Ma; Qiaolei Wang; Hao Zhang; Yuyong Wu; Chunxiao Meng (Marine Drugs)
Aurantiochytrium sp., a heterotrophic microorganism, has received increasing attention for its high production of polyunsaturated fatty acids and has been widely applied in various industries. This study intended to optimize the carotenoid synthesis pathway in Aurantiochytrium sp. by metabolic engineering to increase the carotenoid content. Multi-sourced key enzyme genes involved in lipid synthesis (LPAAT and DGAT) and astaxanthin synthesis (crtZ and crtW) were selected to construct single-gene expression vectors and transformed into Aurantiochytrium sp. The results showed that the overexpression of LPAAT of Phaeodactylum tricornutum in Aurantiochytrium sp. caused an increase of 39.3% in astaxanthin, 424.7% in β-carotene, 901.8% in canthaxanthin, and 575.9% in lutein, as well as a down-regulation of 15.3% in the fatty acid content. Transcriptomics analysis revealed enhanced expression of genes involved in purine and amino acid metabolism in the transformed strains, and the down-regulation of the citric acid cycle led to an increase in the source of acetyl coenzyme A for the production of fatty acids. This study provides strong experimental evidence to support the application of increasing carotenoid levels in Aurantiochytrium sp.